2017
DOI: 10.1038/s41598-017-10987-7
|View full text |Cite
|
Sign up to set email alerts
|

RGMa inhibition with human monoclonal antibodies promotes regeneration, plasticity and repair, and attenuates neuropathic pain after spinal cord injury

Abstract: Traumatic spinal cord injury (SCI) causes a cascade of degenerative events including cell death, axonal damage, and the upregulation of inhibitory molecules which prevent regeneration and limit recovery. Repulsive guidance molecule A (RGMa) is a potent neurite growth inhibitor in the central nervous system, exerting its repulsive activity by binding the Neogenin receptor. Here, we show for the first time that inhibitory RGMa is markedly upregulated in multiple cell types after clinically relevant impact-compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 41 publications
0
48
1
Order By: Relevance
“…Furthermore, intrathecal administration of an antibody against RGMa in a rat SCI model promoted axonal growth and functional recovery, which may be attributed to invasion of microglia and/or macrophages in the site of injury (Hata et al, 2006). Another group developed a systemically administered, human monoclonal antibody against the N-terminus of RGMa, which both neutralized RGMa as well as prevented the RGMa receptor Neogenin from associating with lipid rafts, which is essential for its downstream functions (Mothe et al, 2017). The authors demonstrated that this treatment promoted neuron survival, corticospinal tract axonal regeneration, and improvement in motor function and gait.…”
Section: Modulating Glial Cell-axonal Growth Cone Interactions To Aidmentioning
confidence: 99%
“…Furthermore, intrathecal administration of an antibody against RGMa in a rat SCI model promoted axonal growth and functional recovery, which may be attributed to invasion of microglia and/or macrophages in the site of injury (Hata et al, 2006). Another group developed a systemically administered, human monoclonal antibody against the N-terminus of RGMa, which both neutralized RGMa as well as prevented the RGMa receptor Neogenin from associating with lipid rafts, which is essential for its downstream functions (Mothe et al, 2017). The authors demonstrated that this treatment promoted neuron survival, corticospinal tract axonal regeneration, and improvement in motor function and gait.…”
Section: Modulating Glial Cell-axonal Growth Cone Interactions To Aidmentioning
confidence: 99%
“…SCI is a common central nervous system disorder characterized by destruction or dysfunction of spinal cord caused by trauma or other causes. [42][43][44] SCI can cause a variety of complications that lead to irreversible loss of sensory and motor functions. Recently, the incidence of SCI showed a significant upward trend especially in developing countries, and this is a heavy burden for the patients' family and society.…”
Section: Discussionmentioning
confidence: 99%
“…miR-29a and miR-199B target RGMA and suppress the STAT3 signaling pathway RGMA has been noted to be upregulated in SCI rats and suppressed neurological recovery [10], and STAT3 signaling activation was suggested to inhibit nerve regeneration and repair [21]. Interestingly, either miR-29a or Fig.…”
Section: Overexpression Of Mir-29a or Mir-199b Reduces Neuronal Injurmentioning
confidence: 99%